Proyecto de constitución - Chirinos Soto, Enrique (1994)
This document contains the Proposed Constitution that congressman Enrique Chirinos Soto presented to the Constitutional Congress. It is not an alternative Constitution. Its aim is not to change the views of congressional majority; its purpose was and is to show what in his mind the ideal constitutional text should be.